Effects of enzyme supplementation on growth performance, digestibility of phosphorus, femur parameters and fecal microbiota in growing pigs fed different types of diets - Yin, Yi; Jlali, Maamer; Yu, Bing; Luo, Yuheng; He, Jun; Zheng, Ping; Mao, Xiangbing; Yan, Hui; Wu, Aimin; Bai, Shiping; Devillard, Estelle; Yu, Jie (Frontiers in Veterinary Science, 2024)
A 42-days study was conducted to evaluate the effects of different dietary types (corn-or wheat-soybean meal-based diet) and phytase (Phy) or a multi-carbohydrase and phytase complex (MCPC) supplementation on growth performance, digestibility of phosphorus (P), intestinal transporter gene expression, plasma indexes, bone parameters, and fecal microbiota in growing pigs. Seventy-two barrows (average initial body weight of 24.70 ± 0.09 kg) with a 2 x 3 factorial arrangement of treatments and main effects of diet type (corn-or wheat-soybean meal-based-diets) and enzyme supplementation (without, with Phy or with MCPC). Each group was designed with 6 replicate pens. The MCPC increased (P < 0.05) average daily gain (ADG) and final body weight (BW). A significant interaction (P = 0.01) was observed between diet type and enzyme supplementation on apparent total tract digestibility (ATTD) of P. The ATTD of P was higher (P < 0.05) in wheatsoybean meal-based diets compared to cornsoybean meal-based diets. Compared with the corn-soybean meal-based diet, the relative expression of SLC34A2 and VDR genes in the ileum and SLC34A3 in jejunum of growing pigs fed the wheat-soybean meal based diet was lower (P < 0.05). The MCPC significantly reduced (P < 0.05) the relative expression of TRPV5 and CALB1 genes in the ileum and increased the expression of CALB1 in the duodenum compared to control diet. The phytase increased (P < 0.05) the relative expression of SLC34A1 gene in the duodenum in comparison to control diet and MCPC-supplemented diet. The Ca and P contents in plasma from pigs fed corn-soybean meal-based diet were higher (P < 0.05) than those from pigs fed wheat-soybean meal-based diet, and the parathyroid hormone (PTH) and calcitonin (CT) concentrations were lower (P < 0.05) than those fed wheat-soybean meal-based diet. The content of Ca and P in the femur and the bone strength of pigs in the corn-soybean meal group were significantly higher (P < 0.05) than those in the wheat-soybean meal groups. The phytase increased (P < 0.05) the Ca and P content and bone strength of the femur. Additionally, diet type and both enzymes significantly improved fecal microbial diversity and composition.